Advances in intraocular techniques in the treatment of retinal detachments arising from holes of the posterior pole. - Binder, S (1983)
Two groups of retinal detachments arising from macular holes were compared. The first group consisted of 27 consecutive cases operated upon during the years 1972-7 by various techniques (encircling and hemi-encircling procedures, scleral resection, scleral pocket, and silver clip). The second group consisted of 18 consecutive cases operated upon in the years 1978-81 by pars plana vitrectomy to release vitreous traction or make intraocular manoeuvres possible. In all cases of the second group an intraocular gas bubble was used to tamponade the macular hole, and the hole was coagulated only if necessary. There was not only a significantly better anatomical result in the second group, but the functional results were more favourable. Two-thirds of the eyes of the second group reached a visual acuity between 6/12 and 6/48, while in the first group none of the eyes gained a better vision than 6/60. The reading vision in 2/3 of the first group was negligible, while nearly half of the cases in the second group reached useful acuity between Jaeger 3 and 10.